Facile syntheses, characterization, and physical properties of sulfur-decorated pyran-annulated perylene diimides - Wang, Ran (2020)
Three sulfur‐containing pyran‐annulated perylene diimides (PDIs) were synthesized from commercially available PDIs through a nucleophilic substitution/cyclization reaction sequence. The as‐synthesized compounds were fully characterized by 1H and 13C NMR, and FT‐IR spectroscopy, as well as HRMS and TGA. The as‐prepared PDI derivatives exhibited significantly narrow HOMO–LUMO band gaps and high photochemical and thermal stability. Moreover, these materials exhibited quite different absorptions and emissions in dichloromethane, which were in agreement with the DFT‐calculated results.